Modeling One‐ and Two‐Photon Excitation of 4′‐(Hydroxymethyl)‐4, 5′, 8‐trimethylpsoralen in Complex with DNA: Solving Electron Spill‐Out Problems in Polarizable QM/MM Calculations. Issue 3 (11th February 2021) - Attia, Amr A. A.; Reinholdt, Peter; Kongsted, Jacob
Abstract: The polarizable embedding (PE) method is a fully self‐consistent fragment‐based QM/MM approach that uses advanced polarizable force fields and can be applied for various environments, including solvents and DNA. However, lack of proper electronic description of the MM environment can result in electron density leakage from the QM to the MM region, an effect known as electron spill‐out (ESO). ESO can be avoided by applying effective core potentials (ECPs) on MM atoms in PE (PE‐ECP) or by including repulsion operators to model the orthogonality between the two regions, as in the polarizable density embedding (PDE) approach. In this study, the one‐ and two‐photon absorptions of 4′‐(hydroxymethyl)‐4, 5′, 8‐trimethylpsoralen in complex with DNA and in aqueous solution are investigated. The effect of the missing non‐electrostatic repulsion of the MM region on result accuracy is showcased. While ESO errors are not readily visible for one‐photon absorption spectra, they become significant when computing two‐photon absorption, as more than one excited state is considered. Including ECPs on environment atoms sufficiently addresses the ESO problem, yielding correct structure for excited states. Comparisons with the more advanced PDE model show that PE‐ECP leads to qualitatively correct one‐ and two‐photon absorption spectra. Abstract : One‐ and two‐photon absorption spectra for a psoralene derivative are modeled in aqueous solution and in complex with DNA using the polarizable embedding potential scheme in QM/MM settings. Electron spill‐out errors become significant when computing two‐photon absorption spectra. Including effective core potentials on environment atoms addresses ESO, yielding qualitatively correct spectra as confirmed by the polarizable density embedding method.